Dual-Functional Energy Harvesting and Low-Frequency Vibration Attenuation: Electromagnetic Resonant Shunt Series Quasi-Zero-Stiffness Isolators - Qingchao Yang; Zhaozhao Ma; Ruiping Zhou; Heow Pueh Lee; Kai Chai (Applied Sciences, 2023)
In recent times, there has been a significant focus on electromagnetic resonant shunt damping (ERSD) and quasi-zero-stiffness vibration isolators (QZS VI) as prominent solutions for vibration mitigation or energy harvesting. In this paper, an innovative retrofittable model is proposed for dual-functional energy harvesting and low-frequency vibration attenuation by combining the ERSD and two-stage quasi-zero-stiffness vibration isolator (TQZS VI). The viscous dissipative element between the TQZS VI upper and lower layers is implemented using an electromagnetic shunt transducer that is connected in parallel with a resonant RLC (resistor–inductor–capacitor) circuit. Firstly, the mathematical model of the electromagnetic resonant shunt series quasi-zero-stiffness isolator (ERS-TQZS VI) is developed. Then, the magnitude-frequency response equations of the ERS-TQZS VI system are approximately solved using the harmonic balance method (HBM) in combination with the pseudo-arc-length method (PLM). The analytical approach is validated using numerical simulations. Moreover, the force transmissibility and output power of the ERS-TQZS VI are defined, and detailed parametric analysis for energy harvesting and low-frequency vibration attenuation is performed to assess the critical design parameters that result in optimal performance of the ERS-TQZS VI. The results demonstrate that the ERS-TQZS VI exhibits a significant reduction in resonance peaks of low-frequency vibration while simultaneously enabling effective vibration energy harvesting.